Original paperTopical steroid therapy in atopic dermatitis in theory and practice - Jeziorkowska, Renata; Sysa-Jędrzejowska, Anna; Samochocki, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Topical glucocorticosteroids (GCSs) are commonly used in treatment of atopic dermatitis (AD). Aim : To assess the patients’ compliance with the recommended instructions of the therapy. Material and methods : The study involved 141 adult AD patients. The clinical course of AD and its treatment with GCSs during the last year were analysed. Results: In the periods of exacerbation the lesions involved 10–50% of the skin surface area. Outpatient treatment in specialised dermatological and/or allergology clinics was given to 93% of the study subjects. Sixty-five out of 141 patients regularly attended medical control examinations. Glucocorticosteroids, mostly very potent ones (70.2%), were applied to all the subjects. 66.7% of patients obtained no information about their medications’ anti-inflammatory potential. The substances were applied more frequently than twice daily by 36.4% of the patients. Seventy-two of 141 subjects applied GCSs both temporarily and in the long-term treatment, for 8.3 weeks on average. In the long-term treatment, in which very potent GCSs predominated (70.7%), no one used intermittent therapy. One hundred and thirty patients introduced their own modifications to the instructions concerning GCSs use, among which 37.7% changed the site of application, 58.5% prolonged the duration of application and 49.5% shortened it or occasionally temporarily withdrew the prescribed drug. None of the patients knew the fingertip unit method of dose assessment. Apart from steroid therapy, 56.7% of the patients carried out regular care treatment. Conclusions : The AD patients need to be thoroughly educated by the medical staff in the topical GCSs therapy in atopic dermatitis.